Pelatihan Pembuatan Alat Permainan Edukatif (APE) dari Barang Bekas untuk Mengurangi Sampah Bagi Guru Raudlatul Athfal - Anti Isnaningsih; Iys Nur Handayani; Risdianto Hermawan; Aprilia Wahyuning Fitri; Habib Hambali; Uswatun Hasanah; Luthfi Aji Ramdani; Nandiyah Hidayah; Ana Roswita Peruminingsih; Dike Amelia (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
Learning media has a role in the learning process. The purpose of this community service activity is to provide understanding and training to early childhood education teachers regarding Educational Game Tools (APE) from used goods to support the learning process. The method used in this service is training for early childhood education teachers at IGRA Kebumen Regency through clusters in each sub-district. The training is carried out in person or face to face for one day divided into three sessions, namely material, practice, and assessment. The results of this service activity are providing an understanding of Educational Game Equipment (APE) from used goods through training to teachers and producing several educational game tools media from used goods which have been presented by participants and have been assessed by the presenters who are lecturers from the Education study program. Early Childhood Ma'arif Nahdlatul Ulama University Kebumen. Keywords: Educational Game Tools (APE), Used Goods, Teachers